2015
DOI: 10.3390/fib3040504
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Reinforcement of Polyolefin Fiber Reinforced Concrete for Infrastructure Applications

Abstract: Abstract:The increase in the use of polyolefin fiber-reinforced concrete (PFRC) is in contrast to the limited amount of published research about its fracture behavior. This study assesses the main mechanical and fracture properties of PFRC by using conventional and self-compacting concrete with various dosages. The results highlight the significant performance of PFRC and revealed that improving its residual strength for small deformations would enhance its use for structural purposes. For that matter, a combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 13 publications
(20 reference statements)
2
17
0
1
Order By: Relevance
“…Focusing on polyolefin fibres manufactured to reinforce concrete elements, recent developments have allowed the plastic industry to obtain polyolefin-based synthetic macro-fibres with improved mechanical properties. This type of fibres has become an alternative to steel fibres, as research has shown in various applied studies (23,32) and research publications (22,31,(39)(40). As the importance of the material durability has emerged, some additional properties of polyolefin fibres have given rise to certain advantages in the construction field if compared with steel fibres.…”
Section: Overview Of Polyolefin Fibresmentioning
confidence: 99%
See 2 more Smart Citations
“…Focusing on polyolefin fibres manufactured to reinforce concrete elements, recent developments have allowed the plastic industry to obtain polyolefin-based synthetic macro-fibres with improved mechanical properties. This type of fibres has become an alternative to steel fibres, as research has shown in various applied studies (23,32) and research publications (22,31,(39)(40). As the importance of the material durability has emerged, some additional properties of polyolefin fibres have given rise to certain advantages in the construction field if compared with steel fibres.…”
Section: Overview Of Polyolefin Fibresmentioning
confidence: 99%
“…This shows one of the future lines to improve the use of fibres in the construction field: the search for the appropriate fibre cocktail for each application. These combinations have been used to reduce the amount of steel (and seeking a more sustainable concrete design) (91) and obtain improved FRC mechanical properties in certain applications (40).…”
Section: Polyolefin Fibres Combined Steel Fibresmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of deep research on nanoparticles and the gradual reduction in manufacturing costs for nanoparticles [33], nanoparticles have been gradually extended to the application of civil engineering owing to their characteristic nano effects [34]. Simultaneously, fiber-reinforced composites are also widely used in the construction and building industry, such as plastic fibers as the only reinforcement for flat suspended slabs [35] and polyolefin fiber-reinforced concrete for infrastructure applications [36,37]. However, currently, systematic studies on PVA fiber-reinforced cementitious composites containing nano-SiO 2 are very rare.…”
Section: Introductionmentioning
confidence: 99%
“…In the fourth group of papers investigating new FRP materials synergies, Alberti et al [11] studied the ability of polyolefin fiber reinforced concrete (PFRC) to improve residual strength following small deformations through a combined use of long, macro-synthetic polyolefin fibers and short, steel-hooked fibers. This combination maintained high-performance properties and reliable fracture behavior and increased the fracture energy of plain concrete 38 times.…”
mentioning
confidence: 99%